Study chemical composition of borsch seasoning during freezer storage - Карбівнича, Тетяна Василівна (Eastern-European Journal of Enterprise Technologies, 2012)
The article is devoted to the examination of chemical composition of borsch flavour in the process of storage at low temperatures. Changes in chemical composition of borsch flavour depending on preliminary treatment are experimentally determined